Poverty and poor education are key determinants of high household food insecurity among populations adjoining forest concessions in the Congo Basin - Donn, P.; Ngondi, J.L.; Chupezi Tieguhong, J.; Midoko Iponga, D.; Tchingsabe, O.; Fungo, R.; Tchatat, M.; Kahindo, J.M. (Springer, 2016)
Background: The trees and non-timber forest products (NTFPs) of the Congo Basin play a key role in alleviating food insecurity among millions of people around the world. Although many studies have been conducted both nationally and regionally on issues of food insecurity in the Congo Basin, little is known on the effects of timber exploitation on household food insecurity statues of forest dependent communities in this region. This study focused on the determination of the principal indicators of household food security status of populations living around six selected forest concessions in the Congo Basin.